Karakteristik Tanah Longsor pada Ruas Jalan Tawaeli-Toboli KM 26+57 - Bulan Azahra; Sriyati Ramadhani; Martini (Paulus Civil Engineering Journal, 2026)
Frequent landslide disasters along the Kebun Kopi road in Central Sulawesi have significantly disrupted public mobility and goods distribution, with 12 recorded incidents throughout 2024. This condition is triggered by slope instability prone to deformation, particularly along the TawaeliToboli road section, where previous research indicated slope movement could exceed 0.5 meters under saturated conditions and heavy traffic loads. Addressing this issue, this study was conducted to analyze soil characteristics at the Tawaeli-Toboli Road KM 26+57 segment through laboratory testing of 8 samples and geophysical investigation. Laboratory test results identified the majority of materials as Poorly Graded Sand with Silt (SP-SM) with low density (dry unit weight 0.33-1.60 g/cm³) and minimal cohesion (0.074-0.141 kg/cm²), while geoelectrical survey revealed a subsurface profile dominated by sand-silt mixture with resistivity values of 42.9-288 Ωm indicating groundwater presence. The combination of fine-grained material properties, loose density, low cohesion, and saturated conditions creates a critical slope failure mechanism, where saturated silt layers act as potential slip surfaces, thus requiring specific mitigation measures to prevent landslides at the study location.